Estudo do comportamento transiente de soluções de carbopol por meios de testes oscilatórios e de tensão imposta em função degrau - Vigano, Guilherme Cosme (2019)
The elatoviscoplastic materials are fluids that have elastic, plastic, viscous and thixotropic properties. They are in our daily lives in food products, cosmetics, oil industry, among others. The literature has several works that since the last century has studied this type of non-Newtonian material, although they are not yet fully understood. Therefore, this dissertation aimed to study the elastoviscoplastic materials through different rheological experiments, such as flow curve, creep test, construction test, destruction test and oscillatory tests. The test fluid used was carbopol solutions at three different concentrations. Results from flow curves shows yield stress of 141 Pa, 225 Pa and 291 Pa for the solution of 1%, 3% and 5%, respectively. Carbopol had thixotropic properties for the three concentrations and structural changes were changes were represented by constitutive model used to characterize the thixotropy. From the results of the oscillatory experiments, SAOS, LAOS and Q-LAOS regimes were used to identify that viscous behaviors overlapped elastic behavior by Jeffreys model interpretations. The main contribution of this work is the experimental approach used, which through oscillatory and non-oscillatory tests allowed us to understand how the elastic, plastic, viscous and thixotropic behavior affect the microstructure of a fluid when subjected to a deformation state.